Analisis Bibliometrik dengan VOSviewer: Penelitian dalam Audit Manajemen Lingkungan - Bunga Puji Lestari; Vania Adisty Hasibuan; Dinda Mustika Triwardani; Sri Wulan Saputri; Siti Rodiah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Environmental management audits are an important element in managing the company's sustainability and performance. The main objective is to analyze the development of research on environmental management audits using a bibliometric approach with the VOSviewer tool. The study identifies key trends, collaboration patterns, and evolving themes in the environmental audit-related literature. Publication data was obtained from Google Scholar using the keyword "environmental audit," which was then analyzed using the Publish or Perish and VOSviewer tools. The study identified a total of 989 papers from 1922 to 2024. The results of the analysis showed that keywords such as "audit," "environmental," and "company" dominated the research network, with clusters reflecting the relationship between audit, sustainability, and company performance. The study also shows an increased focus on corporate transparency and social responsibility. Despite challenges such as differences in regulations and organizational capacity, environmental audits have great potential to improve sustainability practices. This research opens up opportunities to explore the role of auditors and audit committees in improving the transparency of sustainability reports.